Levon's trade [large type] - Dixon, Chuck, 1954- (Dixon, Chuck, 1954- Levon Cade, 2025)
"Levon Cade left his profession behind to work construction. He just wants to live an anonymous life and be a good dad to his daughter. But when a local girl vanishes, he's asked to return to the skills that made him a mythic figure in the shadowy world of counterterrorism. Levon's hunt for the missing college student takes him to the heart of a vicious criminal conspiracy, and his actions create a chain reaction that threatens all he holds dear. It's time for him to return to his trade. And Levon's trade is death."--